A deep analysis into flight delays´ problematic: tendancys, root causes and ultimate implications - Amoreira, Joana Da Rocha Tomé Baptista (2021)
A Deep Analysis into Flight Delays’ Problematic: Tendencies, Root Causes and Ultimate Implications Airline industry has been experiencing a considerable increase in demand over the years. However, one of the biggest challenges currently faced by airlines is the industry’s inability to adjust the supply to demand’s growth, as increase in airports’ capacity is limited. Such result in a higher capacity utilization and, consequently in an increased disruption in processes, being flight delays the main problematic arising from that. Considering this, this study will statistically analyse multiple factors, reaching conclusions on flight delays’ tendencies, root causes and implications ,in order to ultimately provide recommendations to minimize such problematic by turning processes more efficient.